Biological Control to Induced Resistance - A Paradigm Shift in Management of Plant Diseases - S. K. Biswas; Rajendra Prasad (International Journal of Economic Plants)
The biological world is a vast network of living organisms interacting in their natural environment. In a given ecological niche, the interaction between or among the organisms may be symbiotic, mutualistic, competitive or antagonistic. Plant diseases of economically important crops are very important alone cause 13 to 20% annual loss in production. In India, more than 50% of the crop loss is caused due to soil inhabiting micro-organism. Many fungal genera have been recognized in root disease complex causing seed decay, damping off, root rot, seedling blight, colar rot, crown rot, foot rot and wilt. The conventional method of its control is based on direct elimination of the pathogen but researches are going on in search of non-conventional and eco-friendly management measures that can give good return to growers. Therefore, biological control is getting popularity in the coming era. In this context, T. harzianum, T. viride, Aspergillus niger AN-27, C. globosum and P. fluorescens etc, have been used for management of plant diseases. Recently, bio-agents are using as inducers in inducer resistance. Induced resistance is a technique of phyto- immunity has received great attention among the researchers. Various types of biological agents, virulent or avirulent strains of pathogens, plant extracts, crude extracts of bio-agents and chemicals which are not considered as fungicides are used as inducers for induction of resistance in various crops.